Development of Multifaceted Risk Taking and the Relations to Sex Steroid Hormones: A Longitudinal Study. Issue 5 (1st April 2018) - Peper, Jiska S.; Braams, Barbara R.; Blankenstein, Neeltje E.; Bos, Marieke G.N.; Crone, Eveline A.
Abstract : Risk taking is a multidimensional construct. It is currently unclear which aspects of risk‐taking change most during adolescence and if/how sex hormones contribute to risk‐taking tendencies. This study applied a longitudinal design with three time‐points, separated by 2 years, in participants aged 8–29 years (670 observations). The Balloon Analogue Risk Task, a delay discounting task, and various self‐report questionnaires were administered, to measure aspects of risk taking. Longitudinal analyses demonstrated mostly nonlinear age‐related patterns in risk‐taking behavior and approach‐related personality characteristics (peaking in late adolescence). Increased testosterone and estradiol were found to increase risk‐taking behavior and impulsive personality, but decrease avoidance‐like personality. This study demonstrates that risk taking is most pronounced in mid‐to‐late adolescence and suggests that sex hormones accelerate this maturational process.